(untitled) (Global Journal of Human-Social Science, 2014)
This paper offers an alternative oppositional reading against the obvious, dominant taken-for-granted codes of scopophilia by which Aaron Siskind’s "Harlem" photograph is interpreted. The paper draws primarily on the works of French thinkers Roland Barthes and Jean Baudrillard to make the case that the nudity of the Black woman evokes a false sexual pathos and heigthens the fetishization of her body.